Recommendations For Effective Protection of the Equipments Inside the Downhole in the Chegara Field Against Corrosion - Q. Sh. Kenjayev; Norinov Faxriyor Qurbonovich; M. A. Tursunov (Research Parks Publishers, 2021)
At present , the productivity of oil and gas wells directly depends on the development of oil and gas fields. By increasing the operating time of wells at high-sulfur fields and pumping the use of appropriate inhibitors in the well at the West Chegara field.